Penjaminan Hak Cipta Melalui Skema Gadai dan Fidusia - Iswi Hariyani (Fakultas Hukum Universitas Islam Indonesia, 2016)
This study focuses on the issues of firstly whether the Intellectual Property Rights (IPR) particularly copyrights can be used as collateral debt/credit? Second, whether the copyright can be used as collateral debt/credit through a scheme of pawn guarantee? and third, whether copyright can be used as collateral debt/credit through a scheme of fiduciary guarantee? This is a normative research with legislation and conceptual approach. The result of the study concluded that first; Intellectual Property Rights (IPR) in particular copyright has been legalized as the collateral object through fiduciary scheme under Article 16 of Law No. 28, 2014. IPR in the form of tangible material can be bound with the pawn and/or fiduciary guarantee. While the Intellectual Property Rights in the intangible or non-material form can only be bound by fiduciary guarantee. Second, the Copyright in the form of material or tangible objects in the perspective of the Guarantees Law can be used as collateral guarantee through the pawn scheme. However, Law No. 28 of 2014 regulates completely about this matter. Third, the Copyright in the form of intangible or immaterial objects in the perspective of the Guarantee Law can be used as the collateral guarantee through fiduciary scheme as stipulated in Article 16 of Law No. 28, 2014. However, the implementation of these rules in the banking sector is still constrained as there has been no revision of the Bank Indonesia Regulation (PBI) No. 9/6 / PBI / 2007 in terms of the bank credit collateral.